Conversion of coffee and plastics residues into activated carbon by chemical activation with ammonia - Surculento-Villalobos, Rodrigo (2026)
Aiming for the valorization of agricultural biomass residues such as coffee husks and plastics wastes such as polyethylene terephthalate (PET), a method for transforming them into activated carbon by using ammonia chloride as activation agent is presented in this study. Firstly, mixtures of PET waste were processed through a pyrolytic process at different operational conditions through a factorial experimental design. The obtained material with the best characteristics of specific surface area (SSA) and mass yield was obtained at 600 °C and 2.5 hours of treatment. These parameters were then used for performing the activation of coffee husks residues and mixtures of them with PET (in mass rates of 1:1 and 1:2 of PET and biomass, respectively) All the obtained materials were then characterized through a Scanning Electron Microscopy - Energy Dispersive Spectroscopy (SEM–EDS), X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and a Differential Scanning Calorimetry - Thermogravimetric Analysis (DSC–TGA) technique, and other physicochemical properties (particle size, bulk density, humidity content and ash content) were also measured, all properties were then compared with characteristics of commercial activated carbon. The activated carbon obtained from coffee husks residues showed a low specific surface area (SSA) and a higher pyrolysis yield. The mixtures of biomass and PET showed lower SSA and higher pyrolysis yield than the ones obtained from PET. The mixture of 1:1 is the best on SSA and yield. The textural analysis was performed (BET, BJH, XRF, XRD and SEM–EDS) on the samples of pure pet and mixture 1:1. This shows that the method allows the utilization of coffee and PET residues to produce activated carbon in a more sustainable way respect to other methods of activation (the proposed method uses low mass relations 10% and no postprocessing).